2016
DOI: 10.1089/vim.2016.0063
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Prevention Through Antiviral Treatment in Biobreeding Rats

Abstract: A picornavirus (Ljungan virus) has been associated with diabetes in its wild rodent reservoir and in diabetes-prone biobreeding (DP-BB) rats. We attempted to alter the development of diabetes in DP-BB rats using two anti-picornavirus compounds (pleconaril and APO-N039), singly or in combination. Antiviral therapy was initiated 2 weeks before expected onset of diabetes. Pleconaril or APO-N039 alone did not affect the debut of diabetes. However, animals receiving a combination of both compounds were protected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This is especially true for complex procedures that require virus growth in vitro supplemented with genomic and immunologic assays. Nonetheless, the association of enteroviral pathogens with human diseases is gradually becoming unequivocal and the medical community is showing a rising interest in antipicornaviral drugs 60, 61 and vaccines 62 .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for complex procedures that require virus growth in vitro supplemented with genomic and immunologic assays. Nonetheless, the association of enteroviral pathogens with human diseases is gradually becoming unequivocal and the medical community is showing a rising interest in antipicornaviral drugs 60, 61 and vaccines 62 .…”
Section: Discussionmentioning
confidence: 99%
“…We later extended our antiviral investigations using treatment with Pleconaril and an experimental antiviral kinase inhibitor APO-N039. The two compounds showed an additive effect when evaluated in tissue culture [36]. This finding was repeated in the BB rats with Pleconaril and APO-N039 administrated singly only showed marginal delay on diabetes onset, while the combination of both drugs protected all animals for the entire 6-week duration of treatment, suggesting possible virus elimination.…”
Section: Ljungan Virus Associated With Diabetes In Animalsmentioning
confidence: 69%
“…LV belongs to the Parechovirus genus in the picornavirus family and several members of the Parechovirus including Ljunganvirus lack a hydrophobic pocket binding structure on the surface of the VP1 protein [42,43]. Despite this finding, Pleconaril does show antiviral activity to LV in tissue culture [36]. Ribavirin, a nucleotide analogue of guanosine, has broad-spectrum direct antiviral effect on members of the picornavirus family.…”
Section: Ljungan Virus Associated With Diabetes In Animalsmentioning
confidence: 99%
“…In another model of virus-induced T1D in the BB rat, a picornavirus called Ljungan virus was found in a wild rodent population of Scandinavian voles and lemmings to be associated with diabetes onset, and it was also shown to impact diabetes within the DP-BB rat (136). Recently, in an interesting preventative treatment strategy, Niklasson et al treated pre-diabetic rats with a combination of two picornavirusspecific anti-viral agents, pleconaril and an anti-picornavirus kinase inhibitor (APO-N039), and found that although rats were on the dual-therapy regimen they were completely protected against the development of autoimmune diabetes (136). This suggests that early intervention in human patients with the right combination of anti-viral agents may help in delaying or preventing the triggering of T1D.…”
Section: Environmental Triggers Of T1dmentioning
confidence: 99%